2007
DOI: 10.1021/ja0700707
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Photosensitizers for Photodynamic Therapy at Infrared Excitation

Abstract: A new type of photosensitizers used in photodynamic therapy, which is based on photon upconverting nanoparticles, is reported. These photosensitizers are excitable with infrared irradiation, which has several times larger tissue penetration depth than the currently available ones. They are brought close to the target cancer cells through antigen-antibody interaction with good specificity and versatility. The design is also flexible in that various photosensitive molecules can be potentially adopted into the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
426
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 555 publications
(437 citation statements)
references
References 18 publications
3
426
0
8
Order By: Relevance
“…Monodisperse UCNPs with distinct shapes are model systems to advance the understanding of the shape-directed assembly/packing behaviors of nanocolloids, but also open new opportunities in fields such as bioimaging (18,19) and photodynamic therapy (20,49). Programming anisotropic NCs to assemble into desired two-and three-dimensional patterns enables the production of complex nanoscale architectures useful for applications such as solar cells (46) and plasmonic metamaterials (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monodisperse UCNPs with distinct shapes are model systems to advance the understanding of the shape-directed assembly/packing behaviors of nanocolloids, but also open new opportunities in fields such as bioimaging (18,19) and photodynamic therapy (20,49). Programming anisotropic NCs to assemble into desired two-and three-dimensional patterns enables the production of complex nanoscale architectures useful for applications such as solar cells (46) and plasmonic metamaterials (50).…”
Section: Discussionmentioning
confidence: 99%
“…These NCs often possess "peculiar" optical properties [e.g., quantum cutting (16) and photon upconversion (17)], allowing the management of photons that could benefit a variety of areas including biomedical imaging (18,19) and therapy (20), photovoltaics (16,21), solid state lighting (22), and display technologies (23). Colloidal upconversion nanophosphors (UCNPs) are capable of converting long-wavelength near-infrared excitation into short-wavelength visible emission through the long-lived, metastable excited states of the lanthanide dopants (24).…”
mentioning
confidence: 99%
“…UCNP-based PDT nanocomposites are considered promising platforms for cancer therapy due to the non-invasive manner and deep tissue penetration of NIR light, which breaks the dilemma of using UV or visible lights as irradiation source. Since Zhang et al 32 first demonstrated the application of UCNP-based nanocomposite for PDT of bladder cancer cells, recent advances in the integration of UCNPs with PSs such as chlorin e6, Rose Bengal, and IR825 (an NIR-absorbing dye) for their PDT applications in vitro and in vivo have created many excitements. [33][34][35] However, the phototoxic effect of 1 O 2 on PDT is restricted because of a hypoxic condition in tumor tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The application of Ln 3+ -UCNPs as an energy source for exciting photosensitizers has been proposed. [8][9][10][11][12][13] The nanoconstructs, which were prepared using upconverting nanoparticles for the excitation of different photosensitizers, made use of the Er 3+ transitions, 2 H 11/2 , 4 S 3/2 -4 I 11/2 and 4 F 9/2 -4 I 11/2 . The transitions have one major disadvantage, the emission from these transitions does not overlap with the strongest absorption peak, the Soret band, of the photosensitizer presently used, which is at B400 nm.…”
mentioning
confidence: 99%